Cytomegalovirus in Preterm Infants - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1992)
The clinical, radiological and neuropathological findings in 15 premature infants with lethal congenital cytomegalovirus infection were studied at the Departments of Pediatrics and Pathology, University of Texas Southwestern Medical Center, Dallas, TX.